Mental health help-seeking intentions among health workers in the east coast of peninsular Malaysia: Perceived barriers and predictive factors - Muhammad Syafiq Kunyahamu; Aziah Daud; Ijlal Syamim Mohd Basri; Tengku Alina Tengku Ismail; Mohd Faiz Md Tahir (PLoS ONE, 2026)
Introduction Mental health problems among health workers are a growing concern globally, including in Malaysia. Despite the availability of mental health services, some health workers do not seek professional help. This study aims to determine the level of health workers’ intention to seek professional help, examine the barriers they perceive, and identify predictors of mental health help-seeking intention. Methods This cross-sectional study involved 470 health workers in the East Coast region of Peninsular Malaysia. Data was collected using a self-administered questionnaire. Linear regression analysis was employed to identify the predictors of professional help-seeking intention. Results The mean score for mental health help-seeking intention was 4.90 (SD = 1.03). Perceived need for help positively predicted help-seeking intention (B = 0.532, p < 0.001), while perceived stigma barriers negatively predicted help-seeking intention (B = −0.588, p < 0.001). Notable barriers perceived included concerns about perceptions of weakness, feelings of embarrassment, a preference for handling problems independently, and challenges in taking time off work. Conclusions This study highlights the roles of the perceived need for help and perceived stigma barriers in predicting health workers’ help-seeking intentions, offering a basis for targeted interventions and policies to enhance mental health support within Malaysian healthcare settings.